Pelatihan Pengolahan Ikan Patin Menjadi Makanan Variatif dan Produktif di Desa Sawah Kecamatan Kampar Utara Kabupaten Kampar - Tuti Andriani (MENARA RIAU, 2014)
Fish not only obtained through inducement in the river , but in the village of North Rice Kampar Kampar district , which was originally a paddy field farming by residents , most of whom were used as fish ponds . According to residents there , farming is not inherited by their parents in advance to the younger generation so that it appears a new innovation , fields used as fish ponds . So most of the village was originally paddy is now a fish pond . The fish teresbut , usually sold to the agent who came to the village. Through community service programs such as training catfish processing into food varied and productive , can be an alternative to improve the economy and public health in general . because these fish ( especially catfish ) can be processed into various forms of food varied and productive